DETERMINAN MINAT BERINVESTASI PADA SAHAM SYARIAH: PERAN PERSEPSI, PENGETAHUAN DASAR INVESTASI DAN KEMAMPUAN FINANSIAL MAHASISWA - APRILIA, NUR; NADILLA, TRIE; MARDHIAH, AINUN; NURHAYATI, NURHAYATI (Universitas Dharmawangsa, 2026)
ABSTRACT This study aims to determine the effect of perception, basic knowledge of students and financial ability on interest in investing in sharia stocks. This research method is quantitative. Data was taken from 53 respondents of students of the Faculty of Islamic Economics and Business (FEBI) UIN Sultanah Nahrasiyah who attended the Capital Market School Level 1 and Level 2 seminars on May 20 and 31, 2024. The data used are primary data obtained through questionnaires. Data analysis was tested using the SPSS 23 tool, while the analysis method and hypothesis design were carried out through validity tests, reliability tests and classical assumptions. Hypothesis testing using the f test, t test and multiple linear regression equations, the results of the study showed Y = 8,302 + 0,043X1 + 0,222X2 + 0,490X3 + e. Conclusion Perception does not have a significant effect on interest in investing in sharia stocks. Basic Knowledge of Students does not have a significant effect on interest in investing in sharia stocks. Financial Ability has a significant effect on interest in investing in sharia stocks. Other factors such as investment motivation, minimum capital and technological advances, have a greater influence on interest in investing in sharia stocks.